Some Design Considerations For The 6.5 KV Igbt-based Half-bridge Dc/dc Converter - Vinnikov, Dmitri (Eletrônica de Potência, 2008)
The 6.5 kV insulated gate bipolar transistor (IGBT) is a new promising power device for high-voltage high-power applications. Due to its increased voltage blocking capability, the new HV IGBT can serve as a good replacement for GTO and IGCT thyristors in medium or medium-to-high power applications. One of its general application fields is railway traction. The paper discusses design and development considerations of the 50-kW auxiliary power supply (APS) to be used in 3.0 kV DC commuter trains. Focus is on the implementation of 6.5 kV IGBTs in the primary inverter of APS to improve power density, integrity and reliability of the whole system. For instance, analysis and simulation of main functional blocks of a converter for different operation points are described. General design considerations mainly concerning the inverter stage, power transformer and output rectifier are specified in the paper. Some design optimization possibilities are proposed.